Industrial training report: Finance department at The Haven All Suite Resort Ipoh. Special project: determinants of local commercial banks profitability / Nursyaidatul Ain Mohd Norbert - Mohd Norbert, Nursyaidatul Ain (Universiti Teknologi MARA, Perlis, 2023)
This is an industrial training report a student from Universiti Teknologi Mara Cawangan Perlis Kampus Arau, Nursyaidatul Ain Binti Mohd Norbert, who is in the last semester of her bachelor's degree and doing industrial training for 25 weeks. This industrial training began on 22 August 2022 and will end on 10 February 2022 of Finance department at The Haven All Suite Resort Ipoh, Perak. During the internship, I was supervised by Miss Lee Hoon Hooi from Finance department. Do not even forget that I was also advised and supervised by UiTM’s advisor, Puan Noor Hafizha Binti Muhamad Yusuf. I learn a lot of new things during this internship and to some extent, it has opened my eyes to the reality that this is the real picture when entering the world of work. However, in this report, I will cover all of the company's information and data as well as the experiences I had throughout my internship. This report will also include a research study in which we will go over the financial course.